Reproductive workers insufficiently signal their reproductive ability in a paper wasp. (22nd January 2020) - Tsuchida, Koji; Saigo, Takaharu; Asai, Kazuyuki; Okamoto, Tomoko; Ando, Masaki; Ando, Tetsu; Sasaki, Ken; Yokoi, Kakeru; Watanabe, Dai; Sugime, Yasuhiro; Miura, Toru
Abstract: Why workers forfeit direct reproduction is a crucial question in eusocial evolution. Worker reproduction provides an excellent opportunity to understand the mechanism of kin conflict resolution between the queen and workers. We evaluated behavioral and physiological differences among females in the paper wasp Polistes chinensis antennalis to examine why some workers reproduce under queenright conditions. Reproductive workers were old and foraged less early in the season; their cuticular hydrocarbon (CHC) profiles overlapped with those of queens but were significantly different. The distinct CHC profile of the eggs of the queen likely represented a cue for policing against those by workers. Juvenile hormone (JH) and dopamine seemed to be associated with gonadotropic function, and the JH level of reproductive workers was similar to that of the queen. The high JH level of reproductive workers likely facilitated their reproduction even under queenright conditions. Gene expression levels of the queen and reproductive workers differed only in vitellogenin. These results suggest that worker reproduction is facilitated by an increase in JH level; however, CHC is not a fertility-linked signal, but a queen-linked signal; consequently, reproductive workers without a queen-linked signal might be allowed to stay within the colony. Lay Summary: Workers of the paper wasp Polistes chinensis antennalis will lay eggs in the presence of a queen. We hypothesized that these workers have a queen-like phenotype. Therefore, we evaluated the behavioral, physiological, and genetic characteristics of these reproducing workers. Reproducing workers had a similar physiological activity to the queen, but different chemical components. Despite their enhanced reproductive ability, these workers could not be "crowned" as queens due to insufficient cuticular hydrocarbon signaling.